Emotional Intelligence and Oral Expression in Pedagogical Practices: A Systematic Literature Review - Hinojosa, Mayra Alejandra Jiménez; Vásquez Pérez, Gabriel Eduardo; Solano, Soleida Fuentes; Martínez, Indira Perea; Gómez Ojeda, Ubelis del Carmen; Urbáez, Silvana Luz Campo; Paredes, Mayrena Liseth Daza; Jiménez, Antonio Julio Villamizar; Molina, Olger Javier Ruiz (Journal of Posthumanism, 2024)
This article analyzes the relationship between emotional intelligence and oral expression within the context of pedagogical practices, recognizing their direct impact on the comprehensive development of students. The purpose of the study was to understand how these two dimensions’ influence students academic and socio-emotional formation, and how they can be effectively integrated into teaching practice. The methodology employed was qualitative in nature, through an exhaustive documentary review of academic literature published over the last years, with an emphasis on relevant empirical and theoretical studies. The findings show that emotional intelligence significantly enhances oral communication skills by improving emotional self-regulation, empathy, and confidence in verbal interaction. Furthermore, oral expression is highlighted as a fundamental tool for emotional management and the construction of social bonds in the classroom. It is concluded that incorporating pedagogical strategies that integrate both components is essential to promote meaningful learning, collaborative environments, and a more inclusive and humanizing education.